Análises dos dados clínicos e marcadores celulares nas respostas TH1 e TH2 nas diferentes formas clínicas de pacientes com hanseníase - Rodrigues, Ricardo Wilson de Pinho (2017)
There are currently no laboratory tests or even sensitive and effective tests for the early diagnosis of leprosy. The aim of this study was to analyze the clinical characteristics of patients with leprosy and investigate their immunological profile, comparing this with the type of lesion and the presence or absence of scar for BCG vaccine. Statistical analyzes were performed by employing comparative tests (Pearson´s chi-square) to evaluate the variables in different clinical forms, considering 5% of significance level. The results there was emphasis on: Patients from 34 to 53 years in VV clinical form (26.9%); Caucasians in BT clinical form (42.0%); predominance of male in the BV clinical forms (19.0%) and VV (26.9%); presence of scar BCG vaccine with a predominance in the BT clinical form (27.5%); nerves more affected with predominance in the lower limbs in BT clinical form (38%). Significant differences occurred in: lesions with hypochromic predominance in BT clinical form (24.0%); type of lesion with difuse predominance in TT clinical form (28.0%); border of the lesion that is ill-defined dominance in VV clinical form (30.0%); limit of lesion with irregular predominance in VV clinical form (32.0%); immunoreactivity with Th1 predominance in the BT clinical form (41.7%). We conclude that the evaluation of the immunological profile in leprosy patients may contribute to the more detailed diagnosis and possibly with better characterization of prognosis for these individuals.